1998
DOI: 10.1034/j.1600-0412.1998.770607.x
|View full text |Cite
|
Sign up to set email alerts
|

Uterine and umbilical artery velocimetry in pre‐eclampsia

Abstract: Abnormal velocity waveforms in the uterine and umbilical arteries have clinical significance in pregnancies complicated by pre-eclampsia and predict adverse outcome of pregnancy, especially the fetal growth restriction and need for operative interventions during labor and delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 32 publications
1
19
1
Order By: Relevance
“…Previous studies examining uterine artery PI [29,30,31,32,33] and serum PlGF or the sFlt-1 to PlGF ratio [34,35,36,37,38,39] in the late second or early third trimesters of pregnancy have essentially focused on the investigation of women presenting to specialist clinics with signs of hypertensive disorders with the aim of identifying the subgroup that will develop severe disease [29,30,31,32,33,34]. Our study examined the application of biomarkers in routine screening for subsequent development of PE as part of a strategy for a new approach to prenatal care [7].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examining uterine artery PI [29,30,31,32,33] and serum PlGF or the sFlt-1 to PlGF ratio [34,35,36,37,38,39] in the late second or early third trimesters of pregnancy have essentially focused on the investigation of women presenting to specialist clinics with signs of hypertensive disorders with the aim of identifying the subgroup that will develop severe disease [29,30,31,32,33,34]. Our study examined the application of biomarkers in routine screening for subsequent development of PE as part of a strategy for a new approach to prenatal care [7].…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, Doppler studies were carried out in pregnancies presenting with PE or fetal growth restriction reported that the outcome was worse if there was increased, rather than normal, impedance to flow in the uterine arteries [16,17,18,19,20,21,22]. Similarly, studies investigating pregnancies with abnormal uterine artery Doppler at 20-24 weeks' gestation reported that outcome was worse in those with persistence of high impedance to flow during the third trimester compared to those with normalization in flow [23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile it is well known that an elevation of the impedance of uterine blood flow as well as the presence of bilateral more than unilateral notch [4,5] are related to an increased frequency of APA. Several studies [6,7] showed a correlation between notch and birth weight according to the persistence or later disappearance of firsttrimester bilateral notch versus unilateral or no notch.…”
mentioning
confidence: 99%